High-intensity focused ultrasound ablation in the treatment of recurrent ovary cancer and metastatic pelvic tumors: a feasibility study. (1st January 2021) - Lei, Tingting; Guo, Xu; Gong, Chunmei; Chen, Xuelian; Ran, Feng; He, Yuchun; Shi, Qiuling; He, Jia
Abstract: Objective: To explore the feasibility of high-intensity focused ultrasound (HIFU) ablation for treating metastatic pelvic tumors and recurrent ovary cancer. Materials and methods: Eight patients with metastatic pelvic tumors or recurrent ovary cancer were enrolled in this study. Among them, 5 patients had ovarian cancer, 1 had cervical cancer, 1 had endometrial cancer, and 1 had rectal cancer. Six of them received abdominal surgical operation for their primary cancer, no one received radiotherapy. HIFU treatment was performed under conscious sedation. Vital signs were monitored during the procedure, and adverse effects were recorded. Postoperative follow-up was performed to observe pain relief and the improvement of the patient's quality of life. Results: The median age of the patients was 54 (range: 33–76) years, with a total of 12 lesions. The average volume of the lesions was 238.0 cm 3 . Six patients completed 12 months follow-up. Postoperative pain relief rate was 60% (3/5), and the quality of life improved in the short term. The main adverse effect of HIFU was pain in the treated area, with the pain score lower than 4, and all of which was self-relieved within 1 day after HIFU treatment. No serious complications such as skin burn, intestinal perforation, and nerve injury occurred. Conclusion: HIFU is feasible for the treatment of metastatic pelvic tumors or recurrent ovary cancer without serious complications. Therefore, HIFU seems a promising treatment for recurrent ovary cancer, metastatic pelvic tumors from cervical cancer, endometrial cancer, and rectal cancer.